Attendees of Manchester's Lung Health Check pilot express a preference for community-based lung cancer screening. Issue 12 (3rd September 2019) - Balata, Haval; Tonge, Janet; Barber, Phil V; Colligan, Denis; Elton, Peter; Evison, Matthew; Kirwan, Marie; Novasio, Juliette; Sharman, Anna; Slevin, Kathryn; Taylor, Sarah; Waplington, Sara; et al.
Abstract : Manchester's 'Lung Health Check' pilot utilised mobile CT scanners in convenient retail locations to deliver lung cancer screening to socioeconomically disadvantaged communities. We assessed whether screening location was an important factor for those attending the service. Location was important for 74.7% (n=701/938) and 23% (n=216/938) reported being less likely to attend an equivalent hospital-based programme. This preference was most common in current smokers (27% current smokers vs 19% former smokers; Adj OR 1.46, 95% CI 1.03 to 2.08, p=0.036) and those in the lowest deprivation quartile (25% lowest quartile vs 17.6% highest quartile; Adj OR 2.0, 95% CI 1.24 to 3.24, p=0.005). Practical issues related to travel were most important in those less willing to attend a hospital-based service, with 83.3% citing at least one travel related barrier to non-attendance. A convenient community-based screening programme may reduce inequalities in screening adherence especially in those at high risk of lung cancer in deprived areas.